AtNPF2.5 Modulates Chloride (Cl−) Efflux from Roots of Arabidopsis thaliana - Li, Bo; Qiu, Jiaen; Jayakannan, Maheswari; Xu, Bo; Li, Yuan; Mayo, Gwenda M.; Tester, Mark; Gilliham, Matthew; Roy, Stuart J. (Frontiers in Plant Science, 2017)
The accumulation of high concentrations of chloride (Cl–) in leaves can adversely affect plant growth. When comparing different varieties of the same Cl– sensitive plant species those that exclude relatively more Cl– from their shoots tend to perform better under saline conditions; however, the molecular mechanisms involved in maintaining low shoot Cl– remain largely undefined. Recently, it was shown that the NRT1/PTR Family 2.4 protein (NPF2.4) loads Cl– into the root xylem, which affects the accumulation of Cl– in Arabidopsis shoots. Here we characterize NPF2.5, which is the closest homolog to NPF2.4 sharing 83.2% identity at the amino acid level. NPF2.5 is predominantly expressed in root cortical cells and its transcription is induced by salt. Functional characterisation of NPF2.5 via its heterologous expression in yeast (Saccharomyces cerevisiae) and Xenopus laevis oocytes indicated that NPF2.5 is likely to encode a Cl– permeable transporter. Arabidopsis npf2.5 T-DNA knockout mutant plants exhibited a significantly lower Cl– efflux from roots, and a greater Cl– accumulation in shoots compared to salt-treated Col-0 wild-type plants. At the same time, NO3– content in the shoot remained unaffected. Accumulation of Cl– in the shoot increased following (1) amiRNA-induced knockdown of NPF2.5 transcript abundance in the root, and (2) constitutive over-expression of NPF2.5. We suggest that both these findings are consistent with a role for NPF2.5 in modulating Cl– transport. Based on these results, we propose that NPF2.5 functions as a pathway for Cl– efflux from the root, contributing to exclusion of Cl– from the shoot of Arabidopsis.